Cardiac MRI assessment of myocardial perfusion. (May 2014) - Hamirani, Yasmin S; Kramer, Christopher M
ABSTRACT: : Coronary artery disease is the most common cause of mortality and morbidity around the globe. Assessment of myocardial perfusion to diagnose ischemia is commonly performed in symptomatic patients prior to referral for cardiac catheterization. Among other noninvasive imaging modalities, cardiac MRI (CMR) is emerging as a highly sensitive and specific test for myocardial ischemia and infarction. Resting perfusion on CMR is used to evaluate for microvascular obstruction, which is shown to predict adverse left ventricular remodeling and cardiac events after acute myocardial infarction. This article summarizes the current understanding of CMR perfusion.